Management of the patient with esophagogastric junction outflow obstruction. Issue 4 (July 2021) - Shahsavari, Dariush; Malik, Zubair; Parkman, Henry P.
Abstract : Purpose of review: Esophagogastric junction outflow obstruction (EGJOO), defined as elevated integrated residual pressure (IRP) with preservation of esophageal peristalsis, is a common finding on high-resolution esophageal manometry. Recent findings: The recent Chicago classification version 4.0 proposes changes to the criteria for diagnosing EGJOO, making this diagnosis more restrictive to now include elevated IRP in both supine and upright positions (with preservation of esophageal peristalsis), presence of obstructive symptoms, and confirmatory tests for EGJOO, such as timed barium esophagram with barium tablet or functional lumen imaging probe. Summary: Once the diagnosis of EGJOO is established, secondary causes need to be ruled out, especially the use of opioid medications. Upper endoscopy is needed for evaluation of EGJOO patients, though cross-sectional imaging is usually not necessary. Many patients improve without intervention; thus, expectant management is recommended for patients with mild or atypical symptoms. There seems to be a limited role for medical treatment. Botox injection into the lower esophageal sphincter is often used to see if the patient improves before committing to more definitive treatments, such as pneumatic dilation, peroral endoscopic myotomy, or Heller myotomy.